Influence of environmental parameter variations on X‐ray beam intensities: a time‐dependent absorption correction. (1st December 2015) - Weigel, Tina; Leisegang, Tilmann; Zschornak, Matthias; Herrmann, Marco; Rothenberger, Manuel; Wünsche, Andreas; Stöcker, Hartmut; Meyer, Dirk C.
Abstract : Essential to the quality of X‐ray analysis in crystallography, such as diffractometry and spectrometry, is a stable and reproducible X‐ray source. Commonly, different optical elements are utilized to provide a dedicated X‐ray beam. The stable alignment of all these components is a prerequisite in order to reduce aberrations and to achieve high signal‐to‐noise ratios. Besides such aberrations and electronically induced variations of the X‐ray primary beam intensity, the environmental conditions are of particular importance, most prominently the barometric pressure, humidity and temperature. In a qualitative as well as quantitative study, the influence of the environmental conditions on the primary beam intensity of a sealed tube with a Cu anode and their correlations are determined. For a common setup, utilizing a scintillation counter, laboratory as well as external conditions are monitored simultaneously for 28 d. Their individual influence on the X‐ray intensity and their correlations are evaluated by statistical analysis including time lag. By this comprehensive study, experimental intensity variations of up to Δ I / I = 1.153 ± 0.001% are determined during density of air changes of Δρ/ρ = 3.7 ± 0.6%. This is interpreted in terms of air transmission variations of up to T X‐ray = 1.137 ± 0.001% for a typical X‐ray analysis setup due to ambient barometric pressure, temperature and humidity changes for natural mid‐ and long‐term variations. Significant correlations with respect to daily and weekly cycles and in particular with ambient conditions are determined. These results are used for a time‐dependent absorption correction of the measured intensity, which reduces the standard error by about 25%.